Implementasi Channel Bot Telegram (Real Time) COVID-19 di Kalimantan Barat dengan Memanfaatkan API - Muhammad Ullil Fahri (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2020)
This research aims to provide the public with statistical data information about COVID-19, especially West Kalimantan. Data is sent quickly using the Official API of the Indonesian Government. Every time there is a data update from the Government, the bot system will automatically retrieve the data and then send it to the telegram bot channel. System testing has been carried out, it can generate valid information automatically without the need for an admin role, where every time there is the latest updatefrom the government, then the channel bot automatically sends data on COVID-19 specifically for West Kalimantan. Keywords— COVID-19, API , Telegram Bot